2023
DOI: 10.1038/s41380-023-01959-7
|View full text |Cite
|
Sign up to set email alerts
|

MYT1L haploinsufficiency in human neurons and mice causes autism-associated phenotypes that can be reversed by genetic and pharmacologic intervention

Abstract: MYT1L is an autism spectrum disorder (ASD)-associated transcription factor that is expressed in virtually all neurons throughout life. How MYT1L mutations cause neurological phenotypes and whether they can be targeted remains enigmatic. Here, we examine the effects of MYT1L deficiency in human neurons and mice. Mutant mice exhibit neurodevelopmental delays with thinner cortices, behavioural phenotypes, and gene expression changes that resemble those of ASD patients. MYT1L target genes, including WNT and NOTCH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…To date, there are three transgenic mouse models that disrupt different exons of MYT1L that converge on a hyperactivity phenotype, while other behaviors are varied likely because different assays were used 12,13,15 . A study by Weigel et al 14 performed scRNAseq on the neonatal (P0) forebrain from the mice described in Wohr et al 15 and found a decreased number of newly formed neurons in the subventricular zone. Additionally, the authors observed an increased expression of non-neuronal gene expression programs which can perturb neuronal cell identity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, there are three transgenic mouse models that disrupt different exons of MYT1L that converge on a hyperactivity phenotype, while other behaviors are varied likely because different assays were used 12,13,15 . A study by Weigel et al 14 performed scRNAseq on the neonatal (P0) forebrain from the mice described in Wohr et al 15 and found a decreased number of newly formed neurons in the subventricular zone. Additionally, the authors observed an increased expression of non-neuronal gene expression programs which can perturb neuronal cell identity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the widespread expression pattern of MYT1L in neurons, it is unclear if specific neuronal subtypes are more sensitive to MYT1L deficiency. Likewise, previous studies using bulk RNA sequencing have shown that MYT1L deficiency affects genes associated with the cell cycle 11,12,14 , differentiation 9,10 , and proliferation 22 . However, a limitation of bulk sequencing is that it only provides average gene expression data from a mixed population of cells, making it challenging to discern the precise origin of observed differences.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations